RATIONAL AND ADAPTIVE EXPECTATIONS OF ECONOMIC AGENTS IN THE CONTEXT OF THE MONETARY POLICY IN UKRAINE (INNOVATIVE ECONOMY, 2020)
Leshchenko P.A. RATIONAL AND ADAPTIVE EXPECTATIONS OF ECONOMIC AGENTS IN THE CONTEXT OF THE MONETARY POLICY IN UKRAINEPurpose. The purpose of the article is to compare the main theories of economic agents’ expectations for an establishment of the ways to increase the effectiveness of the monetary policy in Ukraine.Methodology of research. General scientific methods were used in the research, in particular: the method of comparisons for determining common and distinctive characteristics, as well as peculiarities in interpreting the postulates of the basic theories for explaining the phenomenon of economic agents' expectations and its further use when selecting monetary policy instruments; a systematic approach - to determine channels of influence and the ability to target the expectations of economic agents within the compared theories.Findings. It is determined that the comparison of the two theories is most reasonable to conduct with the following parameters: information usage, empirical tests, inclusion type for the parameter of expectations in modeling, the way to confirm the postulated hypotheses and estimation of expectations perspectives.The necessity for the central bank of the country to take into account the economic expectations in the choice of monetary policy instruments is substantiated.Recommendations for a further research in the area of interpretation, definition and use of indicators of economic agents’ expectations for the conduct of the monetary policy in Ukraine are given.Originality. The scientific novelty of the research results is to use an integrated approachto the study of the economic agents’ expectations and their interpretation in the context of the central bank’s monetary policy of the country. Practical value. The results of the research increase the effectiveness of the development of predictive models of population expectations and inflation indicators and, therefore, can be used by research institutes for the analysis and forecast-based modeling of economic development and by the central bank for the purposes of its monetary policy.Key words: rational expectations theory, adaptive expectations theory, inflation, monetary policy, inflation expectations, economic agents’ expectations, inflation targeting, inflation expectations targeting.
Keywords: Key words; rational expectations theory; adaptive expectations theory; inflation; monetary policy; inflation expectations; economic agents’ expectations; inflation targeting; inflation expectations targeting.